What do we know about productivity gaps and convergence in EMU economies? - Timo Tyrväinen (Bank of Finland, 1998)
This paper examines labour productivity levels and growth rates in 10 EMU economies: Germany, France, Belgium, Netherlands, Italy, Spain, Austria, Finland, Ireland and Portugal. In general, European economies still lag behind the United States in terms of productivity level.Available estimates indicate that in the tradables sector (mainly manufacturing) Belgium, France, the Netherlands and (perhaps more recently) Finland are the top performers among the European countries.There seems to be more room for catch-up growth in Portugal and Spain.For Ireland, relevant sectoral data were not available.As for the nontradables sector (mainly services), one can only draw tentative conclusions. European economies seem to have improved their performance relative to the US, but there is considerable heterogeneity across the different industrial sectors within each country.Hence there is probably room for sectoral catch-up growth in each of these economies, especially so in Portugal and Ireland, with the least room in Belgium, France and the Netherlands. A "stylized fact" indicates that labour productivity tends to grow faster in the tradables sector.On the other hand, the well-established Balassa-Samuelson hypothesis states that higher sectoral differences in productivity growth tend to generate higher sectoral inflation differentials and these, in turn, induce higher aggregate inflation.Against this backround, it is interesting to note that differentials in sectoral productivity growth rates seem to have been surprisingly similar among the countries studied: they have varied between 2 and 3 percentage points on average during the period studied.The overall view of the paper is that, due to the structural heterogeneity of countries concerned and measurement problems, caution should be exercised in classifying the EMU-countries into high- and low-productivity economies.A fairly certain conclusion of this study is that relative to the US there is still room for catch-up growth in productivity in all the countries, perhaps more so in Ireland, Portugal and Spain.
URN:NBN:fi:bof-20140807671
Keywords: 330; EMU; convergence; productivity; Balassa-Samuelson hypothesis